PERFORMA AYAM KAMPUNG SUPER YANG DIBERI TEPUNG USUS AYAM SEBAGAI SUBTITUSI TEPUNG IKAN - Yahya Ismail; Syahruddin Syahruddin; Srisukmawati Zainudin (Jambura Journal of Animal Science, 2021)
The aim of this research was to analyze the performance of the super native chicken and the optimal level of chicken intestine meal which can substitute fish meal in the feed ration. This study used a completely randomized design (CRD) consisting of 5 treatments and 4 replications. The treatments given were P0 = 10% fish meal + 0% chicken intestine meal in the feed rations, P1 = 7.5% fish meal + 2.5% chicken intestine meal in the feed rations, P2 = 5% fish meal + 5% chicken intestine meal in the feed rations, P3 = 2.5% fish meal + 7.5% chicken intestine meal in the feed ration, P4 = 0% fish meal + 10% chicken intestine meal in the feed ration.The number of super native chickens used in this study was 100 chickens. The results showed that giving chicken intestine meal as a substitute for fish meal in the feed ration had no significant effect (P 0.05) on feed ration consumption, body weight gain, and feed conversion ratio of super native chicken. It can be concluded that giving chicken intestine meal as a substitute for fish meal in the feed ration gives the same performance. Chicken intestine meal can substitute or replace fish meal up to a level of 10% in the feed ration super native chicken.